METABOLIC SYNDROME RELATIONSHIP AND RISK FACTORS ASSOCIATED WITH IMMEDIATE LIFE PATH ENVIRONMENTS - Jefferson, Jadir (Health and Society, 2024)
This review describes how risk factors and adversities predispose to metabolic syndrome and chronic diseases, acting through harmful habits, nutritional changes, toxins, pollutants, inflammations, pathogens and chronic stress. Such conditions are correlated to fast environment driven by life history strategies as responses to the tensions and impacts witnessed, maintaining a close link between risks and metabolic syndromes throughout life and even between generations.